The Role of FveAFB5 in Auxin-Mediated Responses and Growth in Strawberries - Xuhui Wang; Shuo Feng; Jiangshan Luo; Shikui Song; Juncheng Lin; Yunhe Tian; Tongda Xu; Jun Ma (Plants, 2024)
Auxin is a crucial hormone that regulates various aspects of plant growth and development. It exerts its effects through multiple signaling pathways, including the TIR1/AFB-based transcriptional regulation in the nucleus. However, the specific role of auxin receptors in determining developmental features in the strawberry (Fragaria vesca) remains unclear. Our research has identified FveAFB5, a potential auxin receptor, as a key player in the development and auxin responses of woodland strawberry diploid variety Hawaii 4. FveAFB5 positively influences lateral root development, plant height, and fruit development, while negatively regulating shoot branching. Moreover, the mutation of FveAFB5 confers strong resistance to the auxinic herbicide picloram, compared to dicamba and quinclorac. Transcriptome analysis suggests that FveAFB5 may initiate auxin and abscisic acid signaling to inhibit growth in response to picloram. Therefore, FveAFB5 likely acts as an auxin receptor involved in regulating multiple processes related to strawberry growth and development.